A “Fertility Awareness” Survey on Social Media: Men Can Do Better - Hubert Bettinger; Marie Carbonnel; Alexandre Vallée; Catherine Racowsky; Henri-Corto Stoekle; Jean-Marc Ayoubi (American Journal of Men's Health)
Infertility affects 17% of the global population, yet fertility awareness remains low, particularly among younger individuals and men. This study assessed fertility awareness and attitudes toward infertility prevention among French adults of childbearing age, focusing on gender differences. Conducted via social media from March to May 2023, the survey included 322 participants aged 18–43 who had not consulted assisted reproduction centers. Most respondents were women (84%), under 33 (59%), from high socio-professional backgrounds (58%), in relationships (78%), and childless (59%). Significant gender differences emerged regarding desired ages for having a first (women: 30.7 ± 3.5 years vs. men: 32.8 ± 3.8 years; p  = .06) and last child (women: 36.7 ± 3.6 years vs. men: 39.8 ± 4.5 years; p  = .001). Only 55.8% of men correctly identified the female fertility window, compared to 64.1% of women ( p  = .023). Men also showed lower awareness of the timing of female fertility decline ( p  = .043) and underestimated the prevalence of assisted reproductive technologies among heterosexual couples ( p  = .001). In addition, men were less likely to discuss fertility with their doctor (15.4% vs. 35.9%; p  = .004) or express interest in infertility prevention consultations (53.9% vs. 60.8%; p  = .048). These findings suggest a gender gap in fertility awareness, with men generally less informed and engaged in reproductive health discussions. While the small sample size limits generalizability, the results underscore the need for targeted educational efforts to improve fertility knowledge and encourage proactive reproductive health behaviors across genders.